A DESCRIPTIVE STUDY OF THE SHIFT OF ROLES BETWEEN A TEACHER AND STUDENTS IN ENGLISH CLASSROOM DISCOURSE - Doni Ramdhani Suwandi (Journal of English and Education, 2015)
This study was aimed to figure out the exchange patterns during classroom interaction and its relation to the shift of roles of serving primary knower between a teacher and students. Thirty nine students of twelfth grade and an English teacher in a public senior high school in Bandung were involved as the participants. This study employed a descriptive-qualitative method, and the main data were classroom observation transcript and teacher’s interview transcript. The data analysis was done by applying classroom discourse analysis through coding and categorizing utterances of teacher and students into exchange categories proposed by Suherdi (2009). The findings reveal that both Non-Anomalous (Knowledge-Oriented and Action-Oriented) and Anomalous Exchanges (Elliptical, Defective, and Broken) were found in the interaction between the teacher and the students, therefore the exchange categories affect the shift of roles of serving primary knower between teacher and students. With regard to the findings, two exchanges were likely to be dominant among other exchanges throughout four meetings of the lesson; those are DK1-initiated exchanges (30.19%) and A1-initiated exchanges (34.57%).